A Case-Based Personal Travel Assistant for Elaborating User Requirements and Assessing Offers - Coyle, Lorcan; Cunningham, Padraig; Hayes, Conor (Trinity College Dublin, Department of Computer Science, 2002)
This paper describes a case-based approach to user profiling in a Personal Travel assistant (based on the 1998 FIPA Travel Scenario). The ap-proach is novel in that the user profile is made up of a set of cases capturing previous interactions rather than as a single composite case. This has the advan-tage that the profile is always up-to-date and also allows for the borrowing of cases from similar users when coverage is poor. Profile data is retrieved from a database in an XML format and loaded into a case-retrieval net in memory. This case-retrieval net is then used to support the two key tasks of requirements elaboration and ranking offers.
Keywords: Computer Science